Counseling Clients Who Have Experienced Undisclosed Infidelity. (October 2021) - Curtis, Russ; Likis-Werle, Elizabeth; Shelton, Terry
Undisclosed infidelity is when one partner suspects betrayal, but the other partner denies it. While the literature is replete with helping couples heal from disclosed infidelity, very few scholarly articles address working with betrayed partners of undisclosed infidelity. Researchers indicated the accuracy of detecting undisclosed infidelity and the propensity for betrayers to lie when confronted, thus counselors need to be aware of the traumatic effects associated with undisclosed infidelity to skillfully support clients.